PENERAPAN MODEL PEMBELAJARAN GAME BASED LEARNING DALAM PEMBELAJARAN PAI DI SMP PGRI 2 BALIKPAPAN - Fitriana, Fitriana; Iskandar Yusuf (Sindoro: Cendikia Pendidikan, 2025)
This study aims to explore the application of the Game Based Learning learning model in Islamic Religious Education subjects at SMP PGRI 2 Balikpapan. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The subjects of the study included teachers and students of Islamic Religious Education. The results of the study indicate that the Game Based Learning learning model is implemented through the use of interactive games, such as digital quizzes, and simulations designed to improve students' understanding of Islamic Religious Education material. The implementation of the Game Based Learning learning model has succeeded in creating a more interesting and enjoyable learning atmosphere, thereby increasing student involvement and motivation. In addition, this model is also effective in developing students' social skills, such as cooperation and communication. However, this study also identified several obstacles, such as limited technological facilities and the need for training for teachers to master this method. However, adaptation to local conditions allows the implementation of the Game Based Learning learning model to still have a positive impact. This study concludes that Game Based Learning is a relevant and innovative learning model to improve the quality of Islamic Religious Education learning. The researcher suggests increasing the support of technological facilities, training for teachers, and collaboration with parents to support the sustainability of this model.